bahasa indonesia bahasa indonesia: bahasa indonesia - Monawaroh; Mansyur; Rusdi Effendi (UNIVERSITAS MUHAMMADIYAH METRO, 2027)
Tiwah is the process of sending off the soul as a religious system in the beliefs of the Dayak Ngaju. This research aims to examine the development of the Tiwah tradition in Kota Baru Village, Kapuas Tengah District, Kapuas Regency, Central Kalimantan, including its processes, functions, and traditional values. This research uses a historical method, which consists of heuristics, criticism, interpretation, and historiography. Research found that the people of Kota Baru Village who carry out Tiwah don't consider a specific religion or a person's background. Tiwah is done together when a family member has passed away and still follows Kaharingan. In daily life, they are expected to maintain good relationships between humans, God, ancestor spirits, and the environment. In conclusion, Tiwah is a religious ritual related to followers of Kaharingan in Kota Baru Village. They believe that after performing this ritual, they will not encounter any misfortune.